Process design and multi-objective optimization of efficient heat utilization distillation based on the influence of pressure and entrainer flow on separation performance. (15th December 2022) - Li, Chen; Zhong, Limei; Wang, Yinglong; Sun, Defeng; Li, Yanan; Cui, Peizhe; Shan, Baoming; Zhu, Zhaoyou; Li, Xin
Abstract: A novel strategy for optimizing extractive pressing-swing distillation for separating pressure-sensitive azeotropic mixtures comprising ethyl acetate/ethanol/butanone was proposed. Dimethyl sulfoxide was selected as the optimal entrainer based on its effect on the vapor–liquid equilibria conditions of the azeotropic mixture. A multi-objective genetic optimization algorithm was used to optimize the economic and gas emissions performance of the process. Pressure and entrainer flow have different effects on the separation of the azeotropes. The operating pressure and entrainer flow were comprehensively optimized as variables. To fully exploit the residual heat, vapor recompression and heat integration were used to improve the process. The improved processes were evaluated based on economic, gas emissions, and exergy analyses. Compared with the extractive pressure-swing distillation process, the total annual cost of the vapor recompression process increased by 5.13%, whereas the gas emission and operation costs decreased by 20.94% and 10.06%. The total annual cost and gas emissions of extractive pressing-swing distillation with heat integration decreased by 17.95% and 26.96%, whilst the exergy efficiency increased by 8.16%. The energy consumption of different control structures in the system subjected to disturbances was compared. The CS2 structure has lower energy consumption than CS1. The energy consumption of the T3 column was greatly reduced. Highlights: EPSD is proposed to separate ethyl acetate/ethanol/butanone azeotrope. Multi-objective optimization is used to optimize parameters of processes. Pressure and entrainer flow are used as variables for comprehensive optimization. The HI-EPSD process has excellent performance.